Implementasi Hidden Curiculum “Tadarus” sebagai Pembentukan Karakter Mahasiswa PBSI UIN Jakarta - Saraswati, Putri; Hindun, Hindun (Universitas Negeri Padang, 2026)
This research was conducted to find out the use of hidden curriculum applied to Indonesian Language and Literature Education (PBSI) students at UIN Jakarta as character building in Educational Psychology courses. The application of hidden curiculum